Influences on the continuity of care for patients with Mycobacterium tuberculosis referred from tertiary and district hospitals - Kallon, Idriss Ibrahim (Department of Public Health and Family Medicine, 2019)
South Africa is one of the countries with the highest burden of Mycobacterium tuberculosis (TB) in the world. The fact that adult patients diagnosed with TB frequently do not attend their primary healthcare clinics after discharge from hospital for continued treatment remains a challenge for public health in South Africa. This qualitative study employed semi-structured interviews, focus group discussions and observations explored the experiences of patients, their families, healthcare workers and policy makers, with continuity of TB care following diagnosis in hospital. The key research question was what factors were shaping patients’ attendance at primary healthcare clinics following TB diagnosis and start of treatment in tertiary and district hospitals. Sub questions were: how did patients diagnosed with TB interpret and act upon their diagnosis and treatment at the tertiary/district hospital? What roles did patients play in the discharge process? What were their home circumstances and experiences at the clinics they were referred to, regarding their registration and follow-up plan? What were the perceptions of patients, healthcare workers and policy makers on what influences patients’ attendance/non-attendance at clinics? The objective of this study was to contribute to our understanding of patients’ experiences and perceptions of treatment of TB and how services to patients could be improved to enhance better continuity of care. I drew on a three-fold theoretical framework: patient-centred care, Foucault’s concept of the 'medical gaze’ and social determinants of health. My study built upon previous and ongoing research on the topic of continuity of care for TB in Cape Town. I argued that problems in the provision of TB services to hospital patients could be understood as failures of the services at the hospital to achieve some of the core components of patient-centered care. Furthermore, I argued that better systems for following-up patients from the hospitals to their homes and clinics would provide more understanding of the challenges patients faced when they have been referred from a tertiary or district hospital to continue with their treatment. Insights gained from qualitatively following patients from diagnosis to discharge and their home circumstances helped to better understand the problem South Africa faced with continuity of care for TB treatment.